Determination of a Testing Threshold for Lumbar Puncture in the Diagnosis of Subarachnoid Hemorrhage after a Negative Head Computed Tomography: A Decision Analysis. (3rd October 2016) - Taylor, Richard Andrew; Singh Gill, Harman; Marcolini, Evie G.; Meyers, H. Pendell; Faust, Jeremy Samuel; Newman, David H.
Abstract: Objective: The objective was to determine the testing threshold for lumbar puncture (LP) in the evaluation of aneurysmal subarachnoid hemorrhage (SAH) after a negative head computed tomography (CT). As a secondary aim we sought to identify clinical variables that have the greatest impact on this threshold. Methods: A decision analytic model was developed to estimate the testing threshold for patients with normal neurologic findings, being evaluated for SAH, after a negative CT of the head. The testing threshold was calculated as the pretest probability of disease where the two strategies (LP or no LP) are balanced in terms of quality‐adjusted life‐years. Two‐way and probabilistic sensitivity analyses (PSAs) were performed. Results: For the base‐case scenario the testing threshold for performing an LP after negative head CT was 4.3%. Results for the two‐way sensitivity analyses demonstrated that the test threshold ranged from 1.9% to 15.6%, dominated by the uncertainty in the probability of death from initial missed SAH. In the PSA the mean testing threshold was 4.3% (95% confidence interval = 1.4% to 9.3%). Other significant variables in the model included probability of aneurysmal versus nonaneurysmal SAH after negative head CT, probability of long‐term morbidity from initial missed SAH, and probability of renal failure from contrast‐induced nephropathy. Conclusions: Our decision analysis results suggest a testing threshold for LP after negative CT to be approximately 4.3%, with a range of 1.4% to 9.3% on robust PSA. In light of these data, and considering the low probability of aneurysmal SAH after a negative CT, classical teaching and current guidelines addressing testing for SAH should be revisited.